Carbon dynamics in mixotrophic phycoremediation of diluted POME using Chlorella vulgaris - Yi Sheng Cheng; Lee Muei Chng; Sim Siong Leong; Swee Pin Yeap; Zeinab Abbas Jawad; Choon Aun Ng; Sethupathi Sumathi; Pey Yi Toh (Algal Research, 2026)

Recovery of phosphate from actual aquaculture wastewater using calcined eggshell under continuous flow condition and its phytotoxicity - Jun Jie Lim; Sumathi Sethupathi; Sin Ying Tan; Nor Ismaliza Mohd Ismail (Aquacultural Engineering, 2026)

Tracking microplastics at the source: a comparative study of fluorescent and FTIR microscopy at a drinking water intake in the Perak River, Malaysia - Irfan Hassan; Sumathi Sethupathi; Mohammad J. K. Bashir; Abdul Latif Ahmad; Purushothaman Parthasarathy (Environmental Monitoring and Assessment, 2025)
Asian rivers are significant carriers of microplastics, posing major environmental and health risks. It is critical to understand the quantity and characteristics of MPs in freshwater, particularly river water used as a source of drinking water. Microplastic pollution in freshwater is a serious issue, but there is surprisingly little data on it, especially in Malaysia. This study aims to investigate the presence and characteristics of microplastics in Perak River water, specifically at a water treatment plant point of abstraction, to understand the quantity and features of MPs in river water used as a source of drinking water, and to inform mitigation measures to reduce riverine MP contamination. Water samples were collected in February and July 2023 from the point of abstraction near the Perak River in Malaysia. We analyzed microplastics based on size, shape, and polymer type using fluorescence and FTIR microscopy. Fluorescence microscopy detected more particles on average, while FTIR microscopy identified 12 distinct polymer and semi-synthetic polymers, with Rayon and PE dominating. Most MPs’ particle sizes ranged from 1 to 10 µm. MPs in the shape of granules and irregulars were often discovered. Study finds FTIR microscopy a more suitable and accurate method for identifying MPs compared to fluorescence microscopy. Numerous unidentified particles were also detected using FTIR and fluorescence microscopy. This research helps authorities to develop mitigation measures to reduce riverine MP contamination in drinking water. Graphical abstract

Amalgamation of g-C3N4/Bi2O2CO3 heterojunction composites for enhanced sunlight photocatalytic removal of carbamazepine - Junaid Ur Rehman Abbasi; Kah Hon Leong; Lan Ching Sim; Chaomeng Dai; Azrina Abd Aziz; Sumathi Sethupathi; Shaliza Ibrahim (Environmental Science and Pollution Research, 2025)

Optimizing Nitrate and Nitrite Recovery from Aquaculture Wastewater Using Coffee Ground Biosorbent: Adsorption Mechanisms and Its Potential as Soil Conditioner - Sin Ying Tan; Sumathi Sethupathi; Kah Hon Leong (Water, Air, & Soil Pollution, 2024)

Microplastics in Asian rivers: Geographical distribution, most detected types, and inconsistency in methodologies - Hsin-Tien Lin; Falk Schneider; Muhamad Afiq Aziz; Keng Yinn Wong; Kantha D. Arunachalam; Sarva Mangala Praveena; Sumathi Sethupathi; Woon Chan Chong; Ayu Lana Nafisyah; Purushothaman Parthasarathy; Shreeshivadasan Chelliapan; Alexander Kunz (Environmental Pollution, 2024)

The role of oxidation on oil palm fiber biochar for ammoniacal nitrogen recovery from aquaculture wastewater - Tanveer Ahmad; Sumathi Sethupathi; Mohammed J.K. Bashir; Sin Ying Tan (Journal of Water Process Engineering, 2024)

A systematic review of microplastics occurrence, characteristics, identification techniques and removal methods in ASEAN and its future prospects - Irfan Hassan; Sumathi Sethupathi; Mohammad J.K. Bashir; Yamuna Munusamy; Chong Woon Chan (Journal of Environmental Chemical Engineering, 2024)

Acid-modified coffee grounds biochar for nitrate and nitrite removal: an optimization via central composite design - Sin-Ying Tan; Sumathi Sethupathi; Kah-Hon Leong; Tanveer Ahmad (International Journal of Environmental Science and Technology, 2024)

Challenges and opportunities in sustaining aquaculture industry in Malaysia - Sin-Ying Tan; Sumathi Sethupathi; Kah-Hon Leong; Tanveer Ahmad (Aquaculture International, 2024)

Suspended Particulate Matter Analysis of Pre and During Covid Lockdown Using Google Earth Engine Cloud Computing: A Case Study of Ukai Reservoir - Arnab Paul; Vignesh K.S.; Atisha Sood; Swastika Bhaumik; Kunwar Abhishek Singh; Sumathi Sethupathi; Arunima Chanda (Bulletin of Environmental Contamination and Toxicology, 2023)

Mechanism and Kinetics of Low Concentration Total Phosphorus and Reactive Phosphate Recovery from Aquaculture Wastewater via Calcined Eggshells - Sin-Ying Tan; Sumathi Sethupathi; Kah-Hon Leong; Tanveer Ahmad (Water, Air, & Soil Pollution, 2022)

Selectivity of SO2 and H2S removal by ethanol-treated calcined eggshell at low temperature - Waseem Ahmad; Sumathi Sethupathi; Gobi Kanadasan; Nursashabila Iberahim (Environmental Science and Pollution Research, 2020)

Optimization of palm oil mill sludge biochar preparation for sulfur dioxide removal - Nursashabila Iberahim; Sumathi Sethupathi; Mohammed J. K. Bashir (Environmental Science and Pollution Research, 2018)